New records of the squat lobster genus Munida Leach, 1820 (Crustacea: Decapoda: Anomura: Munididae) from deep-water off Okinawa Islands, Ryukyu Islands, Japan, with description of a new species - Komai, Tomoyuki; Higashiji, Takuo (Zootaxa, 2016)
Two species of the squat lobster genus Munida Leach, 1820, M. pollioculus n. sp. and M. zebra Macpherson, 1994, are recorded from deep-waters off Okinawa Islands, the Ryukyu Islands, at depths of 1000 m and 495 m, respectively. The new species closely resembles M. clevai Macpherson, 1999 and M. microps Alcock, 1894, but it differs from the latter two in the absence of a proximal spine on the mesial margin of the cheliped dactylus and the more stout dactylus of the second pereopod. Munida zebra is first recorded from the Northwest Pacific, as well as Japanese waters, with its geographical range extended to the north from the previously known southwestern Pacific localities.